The Morbidity in laparoscopic cholecystectomy: 600 case experience - Diez, Julio; Delbene, Roberto; Ferreres, Alberto (Cirugía del Uruguay, 1994)
Laparoscopic cholecystectomy in conjunction with available experience in 600 cases involves a low morbidity procedure in elective surgery and in we/1-trained hands. lts indications have notoriously expanded and its combination with endoscopic surgery enables a correct management of the main biliary pathway. lt is demonstrated that vesicular effraction has less relevance as regards postoperative infections than the release of calculi. The causes and number of conversions is analyzed. lt is concluded that laparoscopic cholecystectomy is the treatment of choice far biliary lithiasis in most cases.